Time to strengthen the governance of new contaminants in the environment - Xiaoli Zhao; Xiaolei Wang; Jia He; Chenglian Feng; Xiaowei Jin; Kenneth M. Y. Leung; Jian Xu; Chengjun Li; Junyu Wang; Shuangliu Liu; Yan Dou; Beidou Xi; et al. (Nature Communications)
Despite existing regulations, many emerging environmental contaminants remain ungoverned, posing serious risks to ecosystems and human health. Here, we outline governance challenges and propose a global roadmap for their regulation. Proactive identification, risk assessment, and international collaboration are urgently needed to close regulatory gaps and ensure a safer, healthier environment for all.